WORK SATISFACTION MEDIATE IMPACT JOB STRESS TO EMPLOYEE PERFORMANCE ON BANK RAKYAT INDONESIA - Rahmayanti, Rima; Sujai, R.Achmad Drajat Aji; Sukandi, Pipin; Hayati, Neuneung Ratna; Sofyandi, Herman; Agustriyana, Darwis; Buana, Dwinto Martri Aji (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2022)
This study has a goal to find out the influence of job stress to employee performance with work satisfaction as mediate variable in Bank Rakyat Indonesia. The method that was used on this study is descriptive research it is research methods that was done to find out independent variable value or more (independent) without made some comparation or combine a variable with the other variable. There are many samples that was researched are 180 respondents that they are employee of Bank Rakyat Indonesia, especially marketing department (marketer) and the technique that was used is non-probability sample technique with purposive sampling approach (it was taking sample based on the specific target). Based on the result of study was obtained conclusion that multiple linear regression equation of influence job stress to employee performance with work satisfaction as mediate variable. Based on the result of this study was state that there was significant influence between job stress to performance, work satisfaction to performance and job stress to work satisfaction. Whereas, simultaneously job stress and work satisfaction have significant influence to employee performance in PT BRI.